IMF Staff papers : Volume 32 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1985)
This paper illustrates the important consequences of the choice of reserve assets. It considers hypothetical international reserve systems based on gold, on one or several national currencies, on an international financial asset that is not a national currency, and on a combination of these assets. The functioning and macroeconomic consequences of these reserve systems depend very much on the predominant exchange rate regime and on the flexibility of countries' prices and wages. The paper concludes that, because a considerable degree of exchange rate flexibility must be expected for some time to come, a gold-standard system does not offer a viable solution and should be ruled out. Under managed floating, with wages and prices inflexible downward, regulation of the amount of reserve creation, either through appropriately functioning market forces or through international surveillance, could make an important contribution to international economic stability. The patterns of private holding and use of historical reserve assets raise the question of whether there can be an important role for the special drawing rights in a future reserve system as long as its potential as a private asset remains undeveloped.